Analyzing the application of National Philosophy of Education (NPE) throughout learning process in higher education institutions (HEI): the students' perspectives - Hassan, Aminuddin; Asimiran, Soaib; Abd Rahman, Fadzilah; Kamarudin, Nurzatulshima (Eurojournals, 2008)
The implementation of education policies which have been prescribed at all levels should be in line with the National Philosophy of Education (NPE). However, most of the issues debated and practiced in Malaysian Higher Learning Institutions (HEI) usually were not directly associated with National Philosophy of Education. University student, for instance, should be able to relate the effective learning outcome with NPE as it had guide towards that. Student's efforts and contributions were really needed to improve on learning outcome with the implementation of NPE. Therefore this study was carried out that involve students in selected public universities in Malaysia and being operated on sample by using self administered questionnaire which will be circulated in residential colleges. This study focused on the effect of NPE elements implementation in public universities in Malaysia. 80 students from various faculties have been identified as sample by using purposive sampling method. The findings of the study revealed that almost all respondents (86%) had good and very good knowledge level of the NPE respectively. The findings carried out also showed that all NPE's elements that had been identified suitable to be applied in public university's context were successfully achieved in students' perspective with an average rating of more than 3.5 in an increasing 1-5 scale measured (least to most). Qualitative data also been obtained to support the level of knowledge and student's perception of NPE's achievement. This qualitative data is in the form of stating the strength and weakness in achieving NPE.